The Trail of Tears - Isaacs, Sally Senzell (Heinemann Library, 2004)
Discover the everyday lives of American Indians living in the East and how and why in the 1830s they were forced from their homelands. Find out what it was like to be captured at home, put in stockades, then made to walk along rough trails to Indian Territ